2014
DOI: 10.5539/jms.v4n3p145
|View full text |Cite
|
Sign up to set email alerts
|

FM Service Delivery and Quality Service Measurement in Public High Rise Residential Buildings in Nigeria: The Use of SERVQUAL and Satisfaction Index

Abstract: This research assessed and compared the delivery of facilities management services in public high rise residential buildings in Lagos, Nigeria. The objectives include the examination of service delivery method, assessment of the quality of service and determination of resident's satisfaction of the FM services. The methodology adopted is quantitative research and data were collected with use of questionnaire. The response options to the questions were ranked using the 5-point Likert scale. A total of 111 quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For instance, a similarity relationship exists between relationship satisfaction, FM service acceptance and word-of-mouth (WOM). This finding shows that customer satisfaction could influence word-of-mouth and intention to repurchase [18,35,37]. According to Figure 7, there is a strong similarity between relationship satisfaction and FM services acceptance.…”
Section: Fm Services Acceptance and Word-of-mouthmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, a similarity relationship exists between relationship satisfaction, FM service acceptance and word-of-mouth (WOM). This finding shows that customer satisfaction could influence word-of-mouth and intention to repurchase [18,35,37]. According to Figure 7, there is a strong similarity between relationship satisfaction and FM services acceptance.…”
Section: Fm Services Acceptance and Word-of-mouthmentioning
confidence: 78%
“…Thus, the service quality (SERVQUAL) model is often applied to FM research to measure customer satisfaction with FM service quality [37,38]. However, the model has been criticised to lack the potential to measure service encounter outcomes [38,39].…”
Section: Effortmentioning
confidence: 99%
“…The feedback handling process can be measured by gauging user satisfaction. In FM service quality assessment, many previous researchers have used the SERVQUAL model to measure user satisfaction (Abu Hassan et al , 2008; Olanrele and Thontteh, 2014; Karunasena et al , 2018) as indicated in Table I, and this model is explained in the next section.…”
Section: Customer Feedback and Service Organisations’ Responsesmentioning
confidence: 99%
“…Different commentators in FM research have used the SERVQUAL model to measure FM service quality and user satisfaction (for example, Abu Hassan et al , 2008, Olanrele and Thontteh, 2014 and Karunasena et al , 2018). For instance, Karunasena et al (2018) adopted the SERVQUAL framework to manage tenant satisfaction in FM service encounters (Figure 1).…”
Section: Application Of the Service Quality Model In Facilities Managementmentioning
confidence: 99%
“…There is therefore a tendency for the investors of multi-unit apartments to be carried away with the returns on their investments at the cost of satisfying the residents of such apartments. Also, multi-unit residential buildings provide for the use of common spaces, utilities, and services, the availability of which is critical to residents' satisfaction (Olanrele and Thontteh, 2014).…”
Section: Introductionmentioning
confidence: 99%